INCREASING STUDENTS’ STOCK OF VOCABULARY THROUGH SONGS AT SMP ANUGRAH TONDANO - Estrivi Tombeng; Sarah Kamagi; Meity Muntuuntu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
To improve students' language skills, the researcher is interested in employing English songs. If teachers use engaging teaching methods, students will be more motivated to learn English. High motivation can thus facilitate pupils' learning. This research aimed at finding out whether the use of songs could increase the students’ stock of vocabulary or not. In conducting this research, quantitative research was used. The subject of this study was one class of the first grade at SMP Anugrah Tondano that consist of 20 students. The instrument of collecting data was in the form pre-test and post-test. The tests were in the form fill in test with missing words and multiple choice. The result of this research showed that the mean scores in the post-test was higher (77) than those of pre-test (40). Which has an increase in scores of (23) between pre-test to post-test. It could conclude that, the use of song was effective to increase students’ vocabulary because it could stimulate students in learning and encourage them to be able to memorize the word